Autistic graduates: graduate capital and employability. Issue 4 (19th May 2022) - Pesonen, Henri V.; Tuononen, Tarja; Fabri, Marc; Lahdelma, Minja
ABSTRACT: An unprecedented number of autistic people are completing university and they frequently face unemployment after graduation. However, research focusing on the forms of graduate capital and their employability is scarce. The focus of existing research has been on non-autistic, or neurotypical, graduates. The human, social, cultural, identity and psychological capital might be different for autistic graduates due to the characteristics of autism. Using a participatory approach, our aim was to examine the five areas of graduate capital in the context of autistic graduates. The study involved semi-structured interviews with 15 autistic university graduates from England, Finland, France and the Netherlands. Data were analysed using theory guided content analysis and 'data-driven' approaches. Findings indicate that the five areas of graduate capital are particularly relevant to autistic graduates, who typically expose gaps in several capital, jeopardising their employability.